COVID-19 outbreak in Brazil: adherence to national preventive measures and impact on people's lives, an online survey - Edlaine Faria de Moura Villela; Rossana Verónica Mendoza López; Ana Paula Sayuri Sato; Fábio Morato de Oliveira; Eliseu Alves Waldman; Rafael Van den Bergh; Joseph Nelson Siewe Fodjo; Robert Colebunders (BMC, 2021)
Abstract Background The first case of COVID-19 infection was diagnosed in Brazil 26th February 2020. By March 16th, physical distancing and confinement measures were implemented by the Brazilian government. Little is known about how these measures were followed up by the Brazilian people and their impact on daily routine. Methods In early April 2020, using an online platform, we organized an online survey among adults living in Brazil about their COVID-19 preventive behavior and impact on their daily routine. Results Data from 23,896 respondents were analyzed (mean age: 47.4 years). Due to COVID-19 restrictions, half (51.1%) of the professionals reported working from home. Regular handwashing was practiced by 98.7% of participants; 92.6% reported adhering to the 1.5-2 m physical distancing rule, but only 45.5% wore a face mask when going outside. While 29.3% of respondents found it relatively easy to stay at home, indoor confinement was extremely difficult for 7.9% of participants. Moreover, 11% of participants were extremely worried about their health during the COVID-19 epidemic. Younger people, male, persons living in a rural area/village or popular neighbourhoods, students and workers reported less preventive behaviour. Conclusion Restrictive measures markedly affected the daily and professional routines of Brazilians. Participants showed a satisfactory level of adherence to national COVID-19 prevention guidelines. Qualitative and follow-up studies are needed to monitor the impact of COVID-19 in the Brazilian society.